Starfished in the sand : developing the theory of planned behaviour to predict intentions to use sunscreen on the beach : a research project presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University, Albany, Auckland, New Zealand - Neil, Tessa Anne (Massey University, 2003)
This study examined the predictive power of the theory of planned behaviour in explaining sunscreen use intentions among beach-goers in New Zealand (n = 148) and the United Kingdom (n = 280). Generally, the theory of planned behaviour performed well with attitudes, subjective norms and perceived behavioural control explaining 54.8% (NZ) and 39.5% (UK) of the variability in intention. In addition to the theory of planned behaviour constructs, several other variables were included to enhance the models predictive power. The concepts of descriptive norm, implementation intentions, outcome expectancy, anticipated regret, past behaviour, global self-esteem and conscientiousness were investigated. Implementation intentions, past behaviour and anticipated regret contributed significantly to the theory of planned behaviour in predicting sunscreen use intentions. In addition, partial mediation of the theory of planned behaviour constructs was found by implementation intentions. Interaction effects were evident between past behaviour and perceived behavioural control in the UK sample. Implications for further investigation of the concept of anticipated regret and including a measure of self-identity are discussed.
Keywords: New Zealanders Attitudes; Human behavior; Psychological aspects; Great Britain British Attitudes; Skin Cancer Prevention; Sunscreens (Cosmetics)